Baseline Indicator for Program Evaluation: Case Study of Millennial Farmer Program in West Java Province - Kurniawan, Dicky Eka; Ningrum, Sinta; Widianingsih, Ida (Universitas Teuku Umar, 2023)
The design of a policy or program evaluation study is both descriptive and analytical. On the one hand, evaluators try to describe what has happened, and on the other hand, try to explain why it happened. To do this, evaluators need to observe what happens before and after the policy or program is implemented. This research aims to describe phenomena related to the agricultural sector in West Java Province before the millennial farmer program was implemented in 2021. Such knowledge will be useful as baseline indicator when assessing the program's performance and impact. This research uses a qualitative approach with a case study design and a literature study review. The data source used is secondary data in the form of previous study and statistical data obtained from the Central Bureau of Statistics (BPS). The results showed that there were six empirical phenomena that described the condition of the West Java agricultural sector before the millennial farmer program was implemented, namely the percentage of young farmers that continued to decline, the low average wage of agricultural workers, the deficit exchange rate of farmers (NTP), the structure of the agricultural sector workforce that shifted towards non-agriculture, the contribution of the agricultural sector to GRDP that decreased, and the position of agriculture as a lagging business sector according to the results of Klassen analysis. These six phenomena can be used as baseline indicators to assess program performance and impact in the next five or ten years.